Emerging Trends in Transmission Electron Microscopy for Medical Applications (Global Journal of Science Frontier Research, 2022)
This paper is an overview of imaging methods used for research and diagnosis that appear in the literature. There are several types of scientific research and imaging modalities, including photography, microscopy, ultrasound, X-ray, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET). The type of images used will depend on the part of the body the researcher wants to see in the image and the types of images readily available to the patient. For many years, medical imaging has played an important role in the early detection, diagnosis, and treatment of cancer and other diseases. In some cases, medical imaging tests are the first step in preventing the spread of cancer by detecting it early, and in many cases the cancer can be cured or eliminated. CT scans, MRIs, ultrasounds and X-ray imaging are very important tools in fighting various diseases. Medical imaging is also used to create accurate computer models of body systems, organs, tissues, and cells used in anatomy and physiology classes in medical school.
Keywords: medical physics; TEM; imaging; acceleration voltage; vacuume and medical imaging